Chapter 5 Vulnerability on Contemporary Stage Embodying Gendered Precarity in Gary Owen's Iphigenia in Splott (2015) and In the Pipeline (2010) - Nicolás Román, Susana (Taylor & Francis, 2024)
After the emergence and development of Performance and Theatre Studies in literary theory, the invisibility of gendered vulnerability denounced through fictional characters has recently raised an interesting debate turning spectators into active participants in the process of negotiating ethical agency. The intersection of vulnerability and precarity in contemporary theatre might offer a challenging approach to be explored due to the ontological connections between the two concepts. Under the light of Alyson Cole's (2016) "All of Us Are Vulnerable, But Some Are More Vulnerable than Others: The Political Ambiguity of Vulnerability Studies, an Ambivalent Critique", Isabell Lorey's (2015) State of Insecurity: Government of the Precarious, and Judith Butler's (2012) "Precarious Life, Vulnerability, and the Ethics of Cohabitation," among other sources, the objective of this chapter is to explore the nexus between gendered forms of vulnerability and other factors inherent to social and economic precarity present in the plays of the Welsh playwright Gary Owen Iphigenia in Splott (2015) and In the Pipeline (2010). The analysis will demonstrate the necessity to (re)structure social bonds according to the condition of mutual cohabitation and shared responsibility by illuminating the complexity of the precarity/vulnerability ambivalence exposed in the plays.